Couples' Anger Dynamics during Conflict: Interpersonal Anger Regulation, Relationship Satisfaction, and Intimate Partner Violence. Issue 4 (28th January 2021) - Slep, Amy M.; Heyman, Richard E.; Lorber, Michael F.; Tiberio, Stacey S.; Casillas, Katherine L.
Abstract : We tested hypotheses about moment‐to‐moment interpersonal influences on anger during couples' conflict, and the association of those anger dynamics with relationship satisfaction and intimate partner violence (IPV). Displayed anger was coded from laboratory observations of cohabiting couples ( N  = 197); experienced anger was assessed via a video‐recall procedure. Credible, but variable, associations were found in which a person's anger display at one moment was linked to change in the partner's anger display and experience in the next moment. Women's anger experience was more strongly influenced by men's anger displays in couples with higher levels of IPV and couples with lower levels of relationship satisfaction. The displayed anger of men who perpetrated higher levels of IPV was more strongly influenced by women's anger displays. Overall, when individuals displayed higher intensity anger, partners reacted with increasingly angry feelings but decreasingly angry displays. Results suggest that anger dynamics relate to dyadic processes and that dynamics relate to important relationship outcomes. Dyadic anger dynamics might prove a worthy intervention target. Resumen: Comprobamos hipótesis acerca de las influencias interpersonales en la ira de un momento a otro durante el conflicto de las parejas y la asociación de esas dinámicas de la ira con la satisfacción con la relación y la violencia de pareja. Se codificó la ira demostrada a partir de observaciones en laboratorio de parejas convivientes (( N = 197); la ira sufrida se evaluó mediante un procedimiento de videollamada. Se hallaron asociaciones creíbles, pero variables, en las cuales la demostración de ira de una persona en un momento estuvo ligada a un cambio en la demostración y la experiencia de ira del otro integrante de la pareja al momento siguiente. La experiencia de ira de las mujeres estuvo influenciada más marcadamente por las demostraciones de ira de los hombres en las parejas con niveles más altos de violencia de pareja y en las parejas con niveles más bajos de satisfacción en la relación. La ira demostrada de los hombres que ejercían niveles más altos de violencia de pareja estuvo influenciada más marcadamente por las demostraciones de ira de las mujeres. En general, cuando las personas demostraron una ira de mayor intensidad, sus parejas reaccionaron con sentimientos de ira cada vez mayores, pero con demostraciones de ira cada vez menores. Los resultados sugieren que la dinámica de la ira se relaciona con procesos diádicos y que esa dinámica se relaciona con importantes resultados para las relaciones. La dinámica diádica de la ira podría ser un objetivo valioso de intervención. 摘要: 我们测试了关于伴侣冲突中即时人际关系对愤怒情绪的影响，以及这些愤怒动态变化与关系满意度和亲密伴侣暴力(IPV)的关联的假设。本研究对197对同居夫妇的实验室观察数据进行解码; 外在的愤怒情绪经历过愤怒的人通过视频回忆过程进行评估。研究人员发现，一个人某一刻的愤怒表现与另一个人下一刻的愤怒表现和经历的变化存在关联，这种关联可信，但也存在变数。在IPV水平较高和关系满意度较低的伴侣中，男性的愤怒表现对女性的愤怒体验有更大的影响。IPV水平较高的男性表现出的愤怒受女性愤怒表现的影响更大。总的来说，当个体表现出更高强度的愤怒时，伴侣的愤怒情绪会越来越强烈，但愤怒的表现会越来越少。结果表明，愤怒动力学与二元过程相关，动力学与重要的关系结果相关。双方二者的愤怒动态过程可能被证明是一个有价值的干预目标。